Chemoprophylactic Anticoagulation Following Lumbar Surgery Significantly Reduces Thromboembolic Events After Instrumented Fusions, Not Decompressions. Issue 3 (1st February 2023) - Cloney, Michael B.; Hopkins, Benjamin; Dhillon, Ekamjeet; El Tecle, Najib; Koski, Tyler R.; Dahdaleh, Nader S.
Abstract : Study Design: Retrospective cohort. Objective: To quantify any reduction in venous thromboembolic events (VTEs) caused by chemoprophylaxis among lumbar surgery patients. Summary of Background Data: Chemoprophylactic anticoagulation (chemoprophylaxis) is used to prevent VTE after lumbar surgery. However, the treatment effect of chemoprophylaxis has not been reported among spine surgery patients, as conventional statistical methods preclude such inferences. Materials and Methods: A total of 1243 consecutive lumbar fusions and 1433 noninstrumented lumbar decompressions performed at our institution over a six-year period were identified, and clinical and demographic data were collected, including on VTE events within 30 days postoperatively. Instrumented lumbar fusions and noninstrumented lumbar surgeries were analyzed separately. Patients who were given chemoprophylaxis (treatment) and controls were matched according to known VTE risk factors, including age, body mass index, sex, diabetes, chronic kidney disease, history of VTE, estimated blood loss, length of surgery, transfusion, whether surgery was staged, and whether surgery used an anterior approach. K-nearest neighbor propensity score matching was performed, and the treatment effect of chemoprophylaxis was calculated. Results: Unadjusted, there was no difference in the rate of VTE between treatment and controls in either population. Baseline clinical and demographic characteristics differed significantly between treatment and control groups. In all, 575 lumbar fusion patients and 435 noninstrumented lumbar decompression patients were successfully propensity score matched, yielding balanced models (Rubin B <25, 0.5<Rubin R <2.0) and >60% reduction in known bias for both populations. The treatment effect of chemoprophylaxis after lumbar fusion in our patient population was a reduction in VTE incidence from 9.4% to 4.2% ( P <0.05), and propensity score adjusted regression confirmed a reduced odds of VTE with chemoprophylaxis (odds ratio=0.37, P =0.035). The treatment effect was not significant for noninstrumented lumbar decompression patients. Conclusion: Among patients undergoing instrumented lumbar fusions, chemoprophylactic anticoagulation causes a significant reduction in VTE, but causes no significant reduction among patients undergoing noninstrumented lumbar decompression.